Broadening the scope of thoracic oncological intervention: a novel minimally invasive method for the diagnosis of primary cardiac lymphoma. (14th May 2015) - Sayal, Karen; Ali, Tariq; Tasker, Angela; Carroll, Nicholas
Abstract : Primary cardiac lymphoma is a rare and aggressive form of non-Hodgkin's lymphoma. It presents with non-specific symptoms which depend on the degree of cardiac infiltration. Appropriate management and early initiation of therapy depends on an understanding of the imaging characteristics and early histological diagnosis. Obtaining histology can be challenging. This is more widely performed using endomyocardial biopsy. However, this technique is associated with recognised morbidity and mortality. We present a novel diagnostic method for the investigation of myocardial and pericardial lesions. This is the first documented case of the diagnosis of primary cardiac lymphoma using endobronchial ultrasound. Endobronchial ultrasound has a well-documented and excellent safety profile.